THE EFFECT OF GIVING MORINGA LEAF EXTRACT (Moringa oleifera) THROUGH DRINKING WATER ON THE ORGANOLEPTIC QUALITY OF BROILER MEAT - I P. B. S. W., Kencana,; Sriyani, N. L. P.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of providing Moringa leaf extract ( Moringa oleifera ) through drinking water on the organoleptic quality of broiler meat. The research was conducted at Banjar Dinas Tiyinggading, Desa Tiyinggading, Selemadeg Barat, Tabanan, Bali, over a period of 35 days, from July 15 to August 20, 2023. The design used was a completely randomized design (CRD) with 4 treatments and 4 replications, each replication consisting of 4 day-old broiler chickens. The treatments were as follows: P0 (broilers given drinking water without Moringa leaf extract as the control), P1 (broilers given drinking water with 2% Moringa leaf extract), P2 (broilers given drinking water with 4% Moringa leaf extract), and P3 (broilers given drinking water with 6% Moringa leaf extract). The observed variables were the organoleptic quality of the meat (color, texture, aroma, flavor, tenderness, and overall acceptance). The results showed that the addition of Moringa leaf extract to drinking water significantly improved (P<0.05) color, aroma, and overall acceptance, while texture, flavor, and tenderness of the broiler meat showed no significant differences (P>0.05). It can be concluded that the addition of Moringa leaf extract at 2%, 4%, and 6% in drinking water improved color, aroma, and overall acceptance, while texture, tenderness, and flavor did not show significant effects.